High-pressure hydrogen production with inherent sequestration of a pure carbon dioxide stream via fixed bed chemical looping. (29th March 2019) - Zacharias, Robert; Visentin, Simone; Bock, Sebastian; Hacker, Viktor
Abstract: The proof of concept for the production of pure pressurized hydrogen from hydrocarbons in combination with the sequestration of a pure stream of carbon dioxide with the reformer steam iron cycle is presented. The iron oxide based oxygen carrier (95% Fe2 O3, 5% Al2 O3 ) is reduced with syngas and oxidized with steam at 1023 K. The carbon dioxide separation is achieved via partial reduction of the oxygen carrier from Fe2 O3 to Fe3 O4 yielding thermodynamically to a product gas only containing CO2 and H2 O. By the subsequent condensation of steam, pure CO2 is sequestrated. After each steam oxidation phase, an air oxidation was applied to restore the oxygen carrier to hematite level. Product gas pressures of up to 30.1 bar and hydrogen purities exceeding 99% were achieved via steam oxidations. The main impurities in the product gas are carbon monoxide and carbon dioxide, which originate from solid carbon depositions or from stored carbonaceous molecules inside the pores of the contact mass. The oxygen carrier samples were characterized using elemental analysis, BET surface area measurement, XRD powder diffraction, SEM and light microscopy. The maximum pressure of 95 bar was demonstrated for hydrogen production in the steam oxidation phase after the full oxygen carrier reduction, significantly reducing the energy demand for compressors in mobility applications. Highlights: Proof of concept for carbon capture while high-pressure hydrogen production. Product gas pressures of up to 30.1 bar in carbon capture mode. Hydrogen and CO2 purity exceeding 99%. 95 bar product gas pressure with full oxygen carrier reduction.